Phonetic imitation by young L2 learners: English VOTs for speakers of Polish - Wieczorek Błażej; Rojczyk Arkadiusz (Psychology of Language and Communication)
Phonetic imitation, understood as adjustment of one’s pronunciation towards that of a model speaker, plays an important role in second language speech learning. The current study was intended to determine the degree to which young native Polish learners of English imitate native English models’ speech, with gender as a potential influencing factor. Thirty-four participants shadowed words with both voiceless /p, t, k/ and voiced /b, d, g/ consonants as onsets, which differ in terms of voice onset time (VOT) in the two languages. Having compared VOT measurements in three tasks, no significant differences were found for /p, t, k/, suggesting no imitation effect regardless of gender, and an apparent increase of prevoicing for /b, d, g/ in the imitation tasks. Some of the null results may be attributed to high baseline values and to the stimuli’s conflicting modalities. Noticeable variability in the data may have masked the true impact of imitative exposure.